Civil war, climate change and development: A scenario study for Sub-Saharan Africa - Conor Devitt; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
We construct a model of development, civil war, and climate change. There are multiple interactions. Economic growth reduces the probability of civil war and the vulnerability to climate change. Climate change increases the probability of civil war. The impacts of climate change, civil war, and civil war in the neighbouring countries reduce economic growth. The model has two potential poverty traps - a climate-change-induced one and a civil-war-induced one - and the two poverty traps may reinforce one another. We calibrate the model to Sub-Saharan Africa and conduct a double Monte Carlo analysis accounting for both parameter uncertainty and stochasticity. We find the following. Although we use the SRES scenarios as our baseline, and thus assume rapid economic growth in Africa and convergence of African living standards to the rest of the world, the impact of civil war and climate change (ignored in SRES) are sufficiently strong to keep a number of countries in Africa in deep poverty with a high probability. Other countries enjoy exponential growth; and some countries may either be trapped in poverty or experience rapid growth. The SRES scenarios were wrong to ignore the impact of climate change and civil war on economic development.
Keywords: 330; civil war; climate change; economic development; Klimaveränderung; Bürgerkrieg; Armut; Entwicklung; Afrika südlich der Sahara